Excavations in Museology (KULT_online, 2010)
The publishing editors of the anthology Museum revisited, Kurt Dröge and Detlef Hoffmann, are specialists in theoretical and practical questions of museum work. Together – Dröge as an ethnologist and Hoffmann as an art historian – they founded the interdisciplinary master course "Museum und Ausstellung" (Museum and Exhibition) at the Carl von Ossietzky University in Oldenburg in 2000. Graduates who took their exams between 2002 and 2009 gave a short introduction to the topic of their master thesis. With a number of examples, mostly from the German museum landscape, the book gives a multiperspectival view of a changing institution.